Ceramic matrix composite air rudder and preparation method thereof

By using ceramic-based composite materials to prepare the air rudder, the problems of high density, high temperature ablation and poor load-bearing performance of traditional air rudder materials are solved, and the air rudder with low density, high temperature ablation and high load-bearing performance are achieved.

CN119569469APending Publication Date: 2025-03-07AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411754148.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Traditional air rudder materials have high density, high temperature ablation resistance and poor load-bearing performance.

Method used

The air rudder is prepared by ceramic matrix composite materials, including the rudder leading edge, rudder skin and rudder frame. Different molding methods of hafnium modified C/SiC ceramic matrix composite and C/SiC ceramic matrix composite are met to meet the temperature and load requirements of each component.

Benefits of technology

The low density, high high temperature ablation resistance and high load-bearing capacity of the air rudder are achieved, while ensuring the reliability of the connection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005165821140000131
    Figure BDA0005165821140000131
Patent Text Reader

Abstract

The invention provides a ceramic matrix composite air rudder and a preparation method thereof. The air rudder comprises a rudder leading edge, a rudder skin and a rudder framework, and the rudder skin and the rudder leading edge are connected with the rudder framework through connecting screws; wherein the rudder leading edge is formed by molding a hafnium modified C / SiC ceramic matrix composite material, and the rudder skin, the rudder skeleton and the connecting screw are all formed by molding a C / SiC ceramic matrix composite material. According to the scheme, all the components are formed by adopting different ceramic matrix composite materials, the rudder leading edge is made of the hafnium modified C / SiC ceramic matrix composite materials, and the composite materials have excellent high temperature resistance and ablation resistance; the rudder framework and the rudder skin are made of C / SiC ceramic-based composite materials, the composite materials enable the rudder framework and the rudder skin to have excellent bearing capacity, meanwhile, the connecting screws are made of the C / SiC ceramic-based composite materials, and the thermal matching performance of the ceramic-based composite materials, the rudder leading edge, the rudder framework and the rudder skin is good. Therefore, the connection between the rudder leading edge and the rudder skeleton and the rudder skin is more reliable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of air rudder preparation, and in particular to a ceramic-based composite material air rudder and a preparation method thereof. Background Art

[0002] The air rudder is an important component of the aerospace vehicle and is the most widely used control component for the aircraft to achieve flight attitude control. During high-speed flight, the aircraft will encounter an extremely harsh aerodynamic heating environment, resulting in extremely high surface temperatures, especially at the root of the leading edge of the rudder, where the temperature can reach over 2000°C; at the same time, the rudder skeleton structure will be subject to a large load in the aerodynamic environment. Therefore, the material of the air rudder must meet the requirements of ablation resistance and strong load-bearing capacity at the same time. However, the traditional air rudder adopts a pure metal solid structure, which has the disadvantages of heavy structural weight and low load-bearing capacity. Although the structure of the air rudder has been optimized through the overall sandwich structure, skin skeleton structure and sandwich structure, it still has the defects of high metal density and weak high-temperature ablation resistance.

[0003] Based on this, there is an urgent need to provide a ceramic-based composite air rudder and a preparation method thereof. Summary of the invention

[0004] The embodiment of the present invention provides a ceramic-based composite air rudder and a preparation method thereof, which can solve the problems of high density, poor high-temperature ablation resistance and poor load-bearing performance of traditional air rudder materials.

[0005] In a first aspect, the present invention provides a ceramic-based composite air rudder, comprising a rudder leading edge, a rudder skin and a rudder frame, wherein the rudder skin and the rudder leading edge are both connected to the rudder frame via connecting screws; wherein the rudder leading edge is formed by using a hafnium-modified C / SiC ceramic-based composite material, and the rudder skin, the rudder frame and the connecting screws are all formed by using a C / SiC ceramic-based composite material.

[0006] Preferably, the density of the ceramic matrix composite material of the rudder leading edge is 2.5-3.6 g / cm 3 The density of ceramic matrix composite materials of rudder frame, rudder skin and connecting screws is 1.8-2.2g / cm 3 .

[0007] Preferably, the hafnium-modified C / SiC ceramic-based composite material is prepared by: using a hafnium-silicon precursor solution as an impregnation solution, and densifying the carbon / carbon matrix by an impregnation pyrolysis method to obtain the hafnium-modified C / SiC ceramic-based composite material.

[0008] Preferably, the C / SiC ceramic-based composite material is prepared by: using silicon alloy powder as reaction powder, and performing high-temperature infiltration on a carbon / carbon matrix by a reaction infiltration method to obtain the C / SiC ceramic-based composite material.

[0009] Preferably, the carbon / carbon matrix is ​​prepared by depositing pyrolytic carbon on the surface of a carbon fiber preform by chemical vapor deposition; wherein the weaving method of the carbon fiber preform is a needle-punched structure, a two-dimensional carbon cloth laminated stitching structure or a fine-woven puncture structure.

[0010] Preferably, in the process of preparing the ceramic matrix composite material of the rudder leading edge and the connecting screw, the weaving method of the carbon fiber preform is a needle-punched structure, and the density of the carbon / carbon matrix is ​​0.6-0.85g / cm 3 ;

[0011] In the process of preparing the ceramic matrix composite material of the rudder frame, the weaving method of the carbon fiber preform is a fine weaving puncture structure, and the density of the carbon / carbon matrix is ​​1.1-1.3g / cm 3 ;

[0012] In the process of preparing the rudder skin ceramic matrix composite material, the weaving method of the carbon fiber preform is a two-dimensional carbon cloth laminated suture structure, and the density of the carbon / carbon matrix is ​​1.1-1.3g / cm 3 .

[0013] Preferably, the hafnium silicon precursor solution comprises polyhafnium oxane, polycarbosilane, a carbon source precursor and an organic solvent; wherein the carbon source precursor is at least one of phenolic resin, furan resin and furfural resin, and the organic solvent is xylene.

[0014] More preferably, the molar ratio of hafnium element to silicon element in the hafnium silicon precursor solution is (4-15):1.

[0015] Preferably, the viscosity of the hafnium silicon precursor solution is 40-180 mPa·s; the temperature of the immersion cracking is 1450-2000° C., and the number of immersion cracking rounds is 9-13 rounds.

[0016] Preferably, the particle size of the silicon alloy powder is 0.1-6 μm, the mass ratio of the carbon / carbon matrix to the silicon alloy powder is 1:(4-9), and the mass ratio of the sum of the amounts of polyhafnium oxide and polycarbosilane to the carbon source precursor and the organic solvent is (8-12):1:1;

[0017] The temperature of the high-temperature infiltration is 1350-1700° C., and the time of the infiltration reaction treatment is 60-90 minutes.

[0018] In a second aspect, the present invention provides a method for preparing the ceramic matrix composite air rudder according to any one of the first aspects, the preparation method comprising:

[0019] (1) Using a hafnium silicon precursor solution as an impregnation solution, the carbon / carbon matrix is ​​densified by an impregnation pyrolysis method to obtain a rudder leading edge ceramic matrix composite material;

[0020] (2) Using silicon alloy powder as reactive powder, high-temperature infiltration was performed on carbon / carbon matrices of different densities by reactive infiltration method to obtain ceramic matrix composites of rudder skin, rudder frame and connecting screws respectively;

[0021] (3) Mechanically processing the ceramic matrix composite materials of the rudder leading edge, the rudder skin, the rudder frame and the connecting screws respectively to obtain the rudder leading edge, the rudder skin, the rudder frame and the connecting screws structural parts;

[0022] (4) Assembling and connecting the rudder leading edge, rudder frame, and rudder skin using the connecting screws to obtain the ceramic-based composite material air rudder.

[0023] Compared with the prior art, the present invention has at least the following beneficial effects:

[0024] In the present invention, considering that the various components in the air rudder are located at different positions and are subjected to different temperatures and loads, the various components are formed by using different ceramic matrix composite materials. Specifically, the leading edge of the rudder uses a hafnium silicon ceramic precursor solution as an impregnation liquid, and reacts with the carbon / carbon matrix through an impregnation pyrolysis method to obtain a hafnium-modified C / SiC ceramic matrix composite material. The mass ablation rate of the ceramic matrix composite material in an oxyacetylene ablation test at 2000°C is less than 0.2×10 -4 g / (cm 2 ·s), so that the leading edge of the air rudder has excellent high temperature resistance and ablation resistance; the rudder frame and rudder skin are prepared by reactive infiltration method to prepare C / SiC ceramic matrix composite materials. The infiltration temperature of this method is low, the damage to the fibers in the carbon / carbon matrix is ​​small, and the mechanical properties of the ceramic matrix composite materials can be largely maintained. The room temperature bending strength of the prepared ceramic matrix composite materials is greater than 300MPa, so that the rudder frame and rudder skin have excellent bearing capacity; at the same time, the connecting screws are C / SiC ceramic matrix composite materials, which have good thermal matching performance with the rudder leading edge, rudder frame and rudder skin, and the breaking load of the prepared connecting screws is greater than 4KN, so that the connection between the rudder leading edge and the rudder frame, and the connection between the rudder skin and the rudder frame is more reliable. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] As mentioned above, due to the disadvantages of heavy weight and low load-bearing capacity of pure metal solid structures, the existing air rudder structures often adopt integral sandwich structures, skin frame structures and sandwich structures. However, this structure still has the defects of high metal density and weak high-temperature ablation resistance. Although the subsequent air rudder with a metal frame combined with a resin-based thermal protection material structure can reduce its density and improve its high-temperature resistance to a certain extent, it still cannot meet the ablation resistance requirements under high temperature conditions, especially above 1500°C. In addition, metal materials and resin-based composite materials have risks such as poor connection reliability due to large differences in thermal properties.

[0027] Based on the above problems, the embodiment of the present invention first considers using C / C composite materials as the main material of the air rudder. However, C / C composite materials are very easy to oxidize in a high-temperature aerobic environment above 400°C. As the flight speed of the new generation of aircraft is getting higher and higher, and the flight time in the atmosphere is getting longer and longer, the pure C / C composite materials will affect the performance of the air rudder components and cannot meet the use requirements of the new generation of aircraft.

[0028] Based on this, an embodiment of the present invention provides a ceramic-based composite air rudder, which includes a rudder leading edge, a rudder skin and a rudder frame, wherein the rudder skin and the rudder leading edge are connected to the rudder frame via connecting screws; wherein the rudder leading edge is formed by using a hafnium-modified C / SiC ceramic-based composite material, and the rudder skin, the rudder frame and the connecting screws are all formed by using a C / SiC ceramic-based composite material.

[0029] In the embodiment of the present invention, considering that the positions of the components in the air rudder are different, the temperatures and loads they bear are also different, the leading edge of the rudder needs to withstand a higher temperature, and the rudder skeleton structure needs to withstand a larger load in an aerodynamic environment. Therefore, based on different performance requirements, the components are formed by using different ceramic matrix composite materials. Specifically, the leading edge of the rudder uses a hafnium silicon ceramic precursor solution as an impregnation liquid, and reacts with the carbon / carbon matrix by an impregnation pyrolysis method to obtain a hafnium-modified C / SiC ceramic matrix composite material. The mass ablation rate of the ceramic matrix composite material in an oxyacetylene ablation test at 2000°C is less than 0.2×10 -4 g / (cm 2·s), so that the leading edge of the air rudder has excellent high temperature resistance and ablation resistance; the rudder frame and rudder skin are prepared by reactive infiltration method to prepare C / SiC ceramic matrix composite materials. This method has low infiltration temperature, simple process, less damage to fibers in the carbon / carbon matrix, and can largely maintain the mechanical properties of the ceramic matrix composite materials. The room temperature bending strength of the prepared ceramic matrix composite materials is greater than 300MPa, so that the rudder frame and rudder skin of the air rudder have excellent bearing capacity; at the same time, the connecting screws are C / SiC ceramic matrix composite materials, which have good thermal matching performance with the rudder leading edge, rudder frame and rudder skin, and the prepared connecting screws have a breaking load of more than 4KN, so that the connection between the rudder leading edge and the rudder frame, and between the rudder skin and the rudder frame is more reliable.

[0030] According to some preferred embodiments, the density of the ceramic matrix composite material of the rudder leading edge is 2.5-3.6 g / cm 3 (For example, it can be 2.5g / cm 3 , 2.8g / cm 3 、3.0g / cm 3 、3.2g / cm 3 , 3.5g / cm 3 or 3.6g / cm 3 ), the density of ceramic matrix composite materials of rudder frame, rudder skin and connecting screws is 1.8-2.2g / cm 3 (For example, it can be 1.8 g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 or 2.2g / cm 3 ).

[0031] Since the aircraft will encounter an extremely harsh aerodynamic environment during high-speed flight, the temperature and load borne by the rudder leading edge and the rudder frame are different. Therefore, in an embodiment of the present invention, the rudder leading edge is formed by using hafnium-modified C / SiC ceramic-based composite material, the rudder frame, rudder skin and connecting screws are made of C / SiC ceramic-based composite material, and the density of the rudder leading edge ceramic-based composite material and the density of the rudder frame, rudder skin and connecting screws ceramic-based composite material are further controlled within the above range, so that the rudder leading edge can have excellent high temperature resistance and ablation resistance, while the rudder frame, rudder skin and connecting screws have higher load-bearing properties. In this way, on the basis of ensuring the lightness of the air rudder, it is further ensured that the air rudder as a whole has the remarkable characteristics of excellent high temperature resistance, ablation resistance, oxidation resistance, strong load-bearing and the like, thereby forming the above-mentioned new air rudder with integrated heat protection and load-bearing functions.

[0032] According to some preferred embodiments, the hafnium-modified C / SiC ceramic-based composite material is prepared by: using a hafnium-silicon precursor solution as an impregnation solution, densifying the carbon / carbon matrix by an impregnation pyrolysis method, and obtaining the hafnium-modified C / SiC ceramic-based composite material.

[0033] In the embodiment of the present invention, the leading edge of the rudder uses a hafnium silicon ceramic precursor as a reactant, and reacts with a carbon / carbon matrix through an impregnation pyrolysis method to obtain a hafnium-modified C / SiC ceramic matrix composite material. The hafnium silicon precursor is first converted into hafnium oxide and silicon oxide during the pyrolysis process. When a certain pyrolysis temperature is reached, the hafnium oxide and silicon oxide can undergo a carbon thermal reduction reaction with the carbon in the system to generate hafnium carbide and silicon carbide. The silicon carbide formed during the pyrolysis process has a certain viscosity and can be filled in the hafnium particles, which is convenient for the flow and bonding of the hafnium particles, so that the hafnium carbide in the system has a better sintering effect, thereby greatly improving the ablation resistance of the composite material, and then making the air rudder have excellent high temperature resistance and ablation resistance.

[0034] According to some preferred embodiments, the hafnium silicon precursor solution contains polyhafnium oxane, polycarbosilane, a carbon source precursor and an organic solvent; wherein the carbon source precursor is at least one of phenolic resin, furan resin and furfural resin, and the organic solvent is xylene; the molar ratio of hafnium element to silicon element contained in the hafnium silicon precursor solution is (4-15):1 (for example, it can be 4:1, 5:1, 8:1, 10:1, 12:1 or 15:1), and the mass ratio of the sum of the amounts of polyhafnium oxane and polycarbosilane to the carbon source precursor and the organic solvent is (8-12):1:1 (for example, it can be 8:1:1, 9:1:1, 10:1:1, 11:1:1 or 12:1:1).

[0035] The experiment of the present invention proves that the reasonable control of the molar ratio of hafnium element to silicon element in the hafnium silicon precursor solution during the impregnation cracking process is conducive to the uniform introduction of hafnium carbide into the carbon / carbon matrix, thereby ensuring that the obtained hafnium-modified C / SiC ceramic-based composite material has excellent high temperature resistance and ablation resistance. For example, if the content of hafnium element is too low, the content of hafnium introduced into the composite material will be too small, which is not conducive to ensuring the good high temperature resistance and ablation resistance of the composite material. If the content of hafnium element is too high, it is not conducive to ensuring the uniformity of hafnium element in the carbon / carbon matrix, which is also not conducive to the good high temperature resistance and ablation resistance of the composite material as a whole.

[0036] According to some preferred embodiments, the viscosity of the hafnium silicon precursor solution is 40-180 mPa·s (for example, it can be 40 mPa·s, 50 mPa·s, 80 mPa·s, 100 mPa·s, 120 mPa·s, 150 mPa·s or 180 mPa·s); the temperature of the impregnation pyrolysis is 1450-2000°C (for example, it can be 1450°C, 1500°C, 1600°C, 1700°C, 1800°C or 2000°C), and the number of impregnation pyrolysis rounds is 9-13 rounds (for example, it can be 9 rounds, 10 rounds, 11 rounds, 12 rounds or 13 rounds).

[0037] In the embodiment of the present invention, by reasonably controlling the viscosity of the hafnium silicon precursor solution, the hafnium silicon precursor solution can be uniformly introduced into the carbon / carbon matrix while ensuring the impregnation efficiency, thereby ensuring that the hafnium-modified C / SiC ceramic-based composite material has excellent high temperature resistance and ablation resistance.

[0038] According to some preferred embodiments, the C / SiC ceramic-based composite material is prepared by: using silicon alloy powder as reaction powder, and performing high-temperature infiltration on a carbon / carbon matrix by a reaction infiltration method to obtain a C / SiC ceramic-based composite material.

[0039] In the embodiment of the present invention, the rudder frame, connecting screws and rudder skin are prepared by a reactive infiltration method. The infiltration temperature of this method is relatively low, and the damage to the fibers in the carbon / carbon matrix is ​​relatively small. In this way, the mechanical properties of the composite material can be largely maintained. The prepared rudder frame and rudder skin ceramic-based composite materials have high room temperature bending strength, thereby enabling the air rudder to have a high load-bearing capacity.

[0040] According to some preferred embodiments, the particle size of the silicon alloy powder is 0.1-6 μm (for example, it can be 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or 6 μm), the mass ratio of the carbon / carbon matrix to the silicon alloy powder is 1:(4-9) (for example, it can be 1:4, 1:5, 1:6, 1:7, 1:8 or 1:9); the temperature of the high-temperature infiltration is 1350-1700°C (for example, it can be 1350°C, 1400°C, 1500°C, 1600°C or 1700°C), and the time of the infiltration reaction treatment is 60-90 min (for example, it can be 60 min, 70 min, 80 min or 90 min).

[0041] In the embodiment of the present invention, by using the silicon alloy powder in the above-mentioned particle size range and the carbon / carbon matrix for reaction infiltration, it is beneficial to ensure that the composite material has good ablation performance and mechanical properties. If the particle size of the silicon alloy powder is too small, it is not conducive to ensuring the good ablation resistance of the composite material. If the particle size of the silicon alloy powder is too large, the composite material formed during the silicon infiltration process will be prone to cracking, which is not conducive to ensuring the good mechanical properties of the composite material. At the same time, the appropriate content of silicon alloy powder and the infiltration temperature are conducive to reducing the damage to the fibers in the carbon / carbon matrix, thereby ensuring the ablation resistance and mechanical properties of the composite material.

[0042] According to some preferred embodiments, the carbon / carbon matrix is ​​prepared by depositing pyrolytic carbon on the surface of a carbon fiber preform by chemical vapor deposition; wherein the weaving method of the carbon fiber preform is a needle-punched structure, a two-dimensional carbon cloth laminated stitching structure or a fine-woven puncture structure.

[0043] It should be noted that the carbon / carbon matrix is ​​prepared by an existing chemical vapor deposition method. In the embodiment of the present invention, the specific process parameters of the chemical vapor deposition method are not specifically limited, and the process parameters commonly used in the prior art can be used.

[0044] According to some preferred embodiments, in the process of preparing the ceramic matrix composite material of the rudder leading edge and the connecting screw, the weaving method of the carbon fiber preform is a needle-punched structure, and the density of the carbon / carbon matrix is ​​0.6-0.85g / cm 3 (For example, it can be 0.6 g / cm 3 , 0.65g / cm 3 , 0.7g / cm 3 , 0.75g / cm 3 , 0.8g / cm 3 or 0.85g / cm 3 ); In the process of preparing the ceramic matrix composite material of the rudder frame, the weaving method of the carbon fiber preform is a fine weave puncture structure, and the density of the carbon / carbon matrix is ​​1.1-1.3g / cm 3 (For example, it can be 1.1 g / cm 3 , 1.15g / cm 3 , 1.2g / cm 3 , 1.25g / cm 3 or 1.3 g / cm 3 ); In the process of preparing the rudder skin ceramic matrix composite material, the weaving method of the carbon fiber preform is a two-dimensional carbon cloth laminated suture structure, and the density of the carbon / carbon matrix is ​​1.1-1.3g / cm 3 (For example, it can be 1.1 g / cm 3 , 1.15g / cm 3 , 1.2g / cm 3, 1.25g / cm 3 or 1.3 g / cm 3 ).

[0045] Taking into account that the temperatures and loads to which various components in the air rudder of an aircraft are subjected during high-speed flight are different, in an embodiment of the present invention, in the process of forming each component, a woven carbon fiber preform is respectively used, and the carbon fiber preform is formed into a carbon / carbon matrix with different densities by using a vapor deposition method. Since the leading edge of the rudder is subjected to a high temperature, it is required to have excellent ablation resistance. Therefore, in the embodiment of the present invention, the density of the carbon / carbon matrix formed by the leading edge of the rudder and the connecting screws is relatively low, so that more ceramic materials can be introduced later, thereby ensuring better ablation resistance of the composite material. The rudder frame and the rudder skin, as the main structures of the air rudder, need to withstand a large load. Therefore, in an embodiment of the present invention, the rudder skin and the rudder frame are respectively formed by the carbon fiber preform formed in the above-mentioned manner and the carbon / carbon matrix density with the above-mentioned density. This is beneficial to effectively reduce the molding cost on the basis of ensuring the performance of the rudder frame and the rudder skin.

[0046] The embodiment of the present invention further provides a method for preparing the secondary sizing agent described in any one of the above items, the preparation method comprising:

[0047] (1) Using a hafnium silicon precursor solution as an impregnation solution, the carbon / carbon matrix is ​​densified by an impregnation pyrolysis method to obtain a rudder leading edge ceramic matrix composite material;

[0048] (2) Using silicon alloy powder as reactive powder, high-temperature infiltration was performed on carbon / carbon matrices of different densities by reactive infiltration method to obtain ceramic matrix composites of rudder skin, rudder frame and connecting screws respectively;

[0049] (3) Mechanically processing the ceramic matrix composite materials of the rudder leading edge, the rudder skin, the rudder frame and the connecting screws respectively to obtain the rudder leading edge, the rudder skin, the rudder frame and the connecting screws structural parts;

[0050] (4) Assembling and connecting the rudder leading edge, rudder frame, and rudder skin using the connecting screws to obtain the ceramic-based composite material air rudder.

[0051] In the embodiment of the present invention, different ceramic-based composite materials are first prepared by different preparation methods, and the prepared ceramic-based composite materials are respectively machined to form a rudder leading edge, a rudder frame, a rudder skin and a connecting screw component, and a number of connecting slots matching the connecting screws are processed on the rudder leading edge, the rudder frame and the rudder skin. In this way, the rudder skin is connected and fixed to the rudder frame by the connecting screws, and one end of the rudder frame is connected and fixed to one end of the rudder leading edge by the connecting screws, thereby obtaining a ceramic-based composite air rudder.

[0052] It should be noted that, in the embodiment of the present invention, the processing specifications of the connecting screws used for assembling the rudder leading edge, the rudder skin and the rudder frame are one or more of M6×1.0mm, M6×1.25mm, M8×1.0mm, and M8×1.25mm.

[0053] In order to more clearly illustrate the technical solution and advantages of the present invention, a method for preparing a ceramic-based composite air rudder and the method for preparing the same are described in detail below through several embodiments.

[0054] Embodiment 1:

[0055] Provides a density of 0.7g / cm 3 The carbon / carbon matrix 1 is used for the preparation of the subsequent rudder leading edge and connecting screws; the density is 1.2g / cm 3 Carbon / carbon matrix 2, used for the subsequent preparation of the rudder frame; providing a density of 1.1 g / cm 3 Carbon / carbon matrix 3, used for the subsequent preparation of rudder skin;

[0056] (1) polyhafnium oxane, polycarbosilane and an organic solvent (xylene) are uniformly mixed, and a carbon source precursor (phenolic resin) is added, and stirred at 120 rpm for 15 hours at room temperature (25° C.) to obtain a hafnium silicon precursor solution; wherein the molar ratio of hafnium element to silicon element contained in the hafnium silicon precursor solution is 8:1; and the mass ratio of the sum of the amounts of polyhafnium oxane and polycarbosilane to the amounts of the carbon source precursor and the organic solvent is 10:1:1;

[0057] The carbon / carbon matrix 1 was placed in a hafnium silicon precursor solution and subjected to 10 cycles of impregnation and cracking at 1500 °C to obtain a density of 3.2 g / cm 3 The rudder leading edge is made of ceramic matrix composite material;

[0058] (2) The carbon / carbon matrix 1, the carbon / carbon matrix 2 and the carbon / carbon matrix 3 are placed in a graphite crucible respectively, and are mixed with silicon alloy powder (with a particle size of 1 μm) at a mass ratio of 1:5, and reacted and melt-infiltrated at 1500° C. to obtain a connecting screw, a rudder frame and a rudder skin ceramic matrix composite material respectively; wherein the density of the connecting screw ceramic matrix composite material is 1.9 g / cm 3 The density of the ceramic matrix composite material of the rudder frame and rudder skin is 1.95g / cm 3 ;

[0059] (3) Mechanically processing the rudder leading edge, rudder skin, rudder frame and connecting screw ceramic matrix composite materials prepared in step 1 and step 2 respectively to obtain rudder leading edge, rudder skin, rudder frame and connecting screw structural parts; wherein the processing specification of the connecting screw is M6×1mm;

[0060] (4) The rudder leading edge, the rudder frame, and the rudder skin are assembled and connected using connecting screws to obtain a ceramic-based composite material air rudder.

[0061] Embodiment 2:

[0062] Provides a density of 0.7g / cm 3 The carbon / carbon matrix 1 is used for the preparation of the subsequent rudder leading edge and connecting screws; the density is 1.2g / cm 3 Carbon / carbon matrix 2, used for the subsequent preparation of the rudder frame; providing a density of 1.1 g / cm 3 Carbon / carbon matrix 3, used for the subsequent preparation of rudder skin;

[0063] (1) polyhafnium oxane, polycarbosilane and an organic solvent (xylene) are uniformly mixed, and a carbon source precursor (phenolic resin) is added, and stirred at 120 rpm for 15 hours at room temperature (25°C) to obtain a hafnium silicon precursor solution; wherein the molar ratio of hafnium element to silicon element contained in the hafnium silicon precursor solution is 10:1; and the mass ratio of the sum of the amounts of polyhafnium oxane and polycarbosilane to the amounts of the carbon source precursor and the organic solvent is 10:1:1;

[0064] The carbon / carbon matrix 1 was placed in a hafnium silicon precursor solution and subjected to 10 cycles of impregnation and cracking at 1500 °C to obtain a density of 3.2 g / cm 3 The rudder leading edge is made of ceramic matrix composite material;

[0065] (2) The carbon / carbon matrix 1, the carbon / carbon matrix 2 and the carbon / carbon matrix 3 are placed in a graphite crucible respectively, and are mixed with silicon alloy powder (with a particle size of 1 μm) at a mass ratio of 1:5, and reacted and melt-infiltrated at 1500° C. to obtain a connecting screw, a rudder frame and a rudder skin ceramic matrix composite material respectively; wherein the density of the connecting screw ceramic matrix composite material is 1.9 g / cm 3 The density of the ceramic matrix composite material of the rudder frame and rudder skin is 1.95g / cm 3 ;

[0066] (3) Mechanically processing the ceramic matrix composite materials of the rudder leading edge, rudder skin, rudder frame and connecting screws prepared in step 1 and step 2 respectively to obtain the rudder leading edge, rudder skin, rudder frame and connecting screw structural parts; wherein the processing specification of the connecting screws is M6×1.25mm;

[0067] (4) The rudder leading edge, the rudder frame, and the rudder skin are assembled and connected using connecting screws to obtain a ceramic-based composite material air rudder.

[0068] Embodiment 3:

[0069] Provides a density of 0.6g / cm 3The carbon / carbon matrix 1 is used for the subsequent preparation of the leading edge of the rudder and the connecting screws; the density is 1.3g / cm 3 Carbon / carbon matrix 2, used for the subsequent preparation of the rudder frame; providing a density of 1.3g / cm 3 Carbon / carbon matrix 3, used for the subsequent preparation of rudder skin;

[0070] (1) polyhafnium oxane, polycarbosilane and an organic solvent (xylene) are uniformly mixed, and a carbon source precursor (phenolic resin) is added, and stirred at 120 rpm for 15 hours at room temperature (25° C.) to obtain a hafnium silicon precursor solution; wherein the molar ratio of hafnium element to silicon element contained in the hafnium silicon precursor solution is 8:1; and the mass ratio of the sum of the amounts of polyhafnium oxane and polycarbosilane to the amounts of the carbon source precursor and the organic solvent is 10:1:1;

[0071] The carbon / carbon matrix 1 was placed in a hafnium silicon precursor solution and impregnated and cracked 10 times at 1600 °C to obtain a density of 3.3 g / cm 3 The rudder leading edge is made of ceramic matrix composite material;

[0072] (2) The carbon / carbon matrix 1, the carbon / carbon matrix 2 and the carbon / carbon matrix 3 are placed in a graphite crucible respectively, and are mixed with silicon alloy powder (with a particle size of 1 μm) at a mass ratio of 1:5, and reacted and melt-infiltrated at 1500° C. to obtain a connecting screw, a rudder frame and a rudder skin ceramic matrix composite material respectively; wherein the density of the connecting screw ceramic matrix composite material is 1.9 g / cm 3 The density of the ceramic matrix composite material of the rudder frame and rudder skin is 1.95g / cm 3 ;

[0073] (3) Mechanically processing the rudder leading edge, rudder skin, rudder frame and connecting screw ceramic matrix composite materials prepared in step 1 and step 2 respectively to obtain rudder leading edge, rudder skin, rudder frame and connecting screw structural parts; wherein the processing specification of the connecting screw is M6×1mm;

[0074] (4) The rudder leading edge, the rudder frame, and the rudder skin are assembled and connected using connecting screws to obtain a ceramic-based composite material air rudder.

[0075] Embodiment 4:

[0076] Provides a density of 0.7g / cm 3 The carbon / carbon matrix 1 is used for the preparation of the subsequent rudder leading edge and connecting screws; the density is 1.2g / cm 3 Carbon / carbon matrix 2, used for the subsequent preparation of the rudder frame; providing a density of 1.1 g / cm 3 Carbon / carbon matrix 3, used for the subsequent preparation of rudder skin;

[0077] (1) polyhafnium oxane, polycarbosilane and an organic solvent (xylene) are uniformly mixed, and a carbon source precursor (phenolic resin) is added, and stirred at 120 rpm for 15 hours at room temperature (25° C.) to obtain a hafnium silicon precursor solution; wherein the molar ratio of hafnium element to silicon element contained in the hafnium silicon precursor solution is 8:1; and the mass ratio of the sum of the amounts of polyhafnium oxane and polycarbosilane to the amounts of the carbon source precursor and the organic solvent is 10:1:1;

[0078] The carbon / carbon matrix 1 was placed in a hafnium silicon precursor solution and subjected to 10 cycles of impregnation and cracking at 1700 °C to obtain a density of 3.3 g / cm 3 The rudder leading edge is made of ceramic matrix composite material;

[0079] (2) The carbon / carbon matrix 1, the carbon / carbon matrix 2 and the carbon / carbon matrix 3 are placed in a graphite crucible respectively, and are mixed with silicon alloy powder (with a particle size of 1 μm) at a mass ratio of 1:5, and reacted and melt-infiltrated at 1500° C. to obtain a connecting screw, a rudder frame and a rudder skin ceramic matrix composite material respectively; wherein the density of the connecting screw ceramic matrix composite material is 1.9 g / cm 3 The density of the ceramic matrix composite material of the rudder frame and rudder skin is 1.95g / cm 3 ;

[0080] (3) Mechanically processing the ceramic matrix composite materials of the rudder leading edge, rudder skin, rudder frame and connecting screws prepared in step 1 and step 2 respectively to obtain the rudder leading edge, rudder skin, rudder frame and connecting screw structural parts; wherein the processing specification of the connecting screws is M8×1mm;

[0081] (4) The rudder leading edge, the rudder frame, and the rudder skin are assembled and connected using connecting screws to obtain a ceramic-based composite material air rudder.

[0082] Embodiment 5:

[0083] Provides a density of 0.6g / cm 3 The carbon / carbon matrix 1 is used for the subsequent preparation of the leading edge of the rudder and the connecting screws; the density is 1.3g / cm 3 Carbon / carbon matrix 2, used for the subsequent preparation of the rudder frame; providing a density of 1.3g / cm 3 Carbon / carbon matrix 3, used for the subsequent preparation of rudder skin;

[0084] (1) polyhafnium oxane, polycarbosilane and an organic solvent (xylene) are uniformly mixed, and a carbon source precursor (phenolic resin) is added, and stirred at 120 rpm for 15 hours at room temperature (25°C) to obtain a hafnium silicon precursor solution; wherein the molar ratio of hafnium element to silicon element contained in the hafnium silicon precursor solution is 13:1; and the mass ratio of the sum of the amounts of polyhafnium oxane and polycarbosilane to the amounts of the carbon source precursor and the organic solvent is 10:1:1;

[0085] The carbon / carbon matrix 1 was placed in a hafnium silicon precursor solution and subjected to 12 cycles of impregnation and cracking at 1800 °C to obtain a density of 3.5 g / cm 3 The rudder leading edge is made of ceramic matrix composite material;

[0086] (2) The carbon / carbon matrix 1, the carbon / carbon matrix 2 and the carbon / carbon matrix 3 are placed in a graphite crucible respectively, and are mixed with silicon alloy powder (with a particle size of 1 μm) at a mass ratio of 1:5, and reacted and melt-infiltrated at 1500° C. to obtain a connecting screw, a rudder frame and a rudder skin ceramic matrix composite material respectively; wherein the density of the connecting screw ceramic matrix composite material is 1.9 g / cm 3 The density of the ceramic matrix composite material of the rudder frame and rudder skin is 1.95g / cm 3 ;

[0087] (3) Mechanically processing the rudder leading edge, rudder skin, rudder frame and connecting screw ceramic matrix composite materials prepared in step 1 and step 2 respectively to obtain rudder leading edge, rudder skin, rudder frame and connecting screw structural parts; wherein the processing specification of the connecting screw is M6×1mm;

[0088] (4) The rudder leading edge, the rudder frame, and the rudder skin are assembled and connected using connecting screws to obtain a ceramic-based composite material air rudder.

[0089] Embodiment 6:

[0090] Example 6 is substantially the same as Example 1, except that in step (1), the molar ratio of hafnium element to silicon element in the hafnium silicon precursor solution is 16:1.

[0091] Embodiment 7:

[0092] Example 7 is substantially the same as Example 1, except that in step (2), the mass ratio of carbon / carbon matrix to silicon alloy powder is 1:3, and the particle size of the silicon alloy powder is 7 μm.

[0093] Embodiment 8:

[0094] Example 8 is basically the same as Example 1, except that in step (1), the rudder leading edge, rudder frame, rudder skin and connecting screws are all made of a material with a density of 1.2 g / cm 3 Carbon / carbon matrix.

[0095] Comparative Example 1

[0096] Provides a density of 0.7g / cm 3 The carbon / carbon matrix 1 is used for the preparation of the subsequent rudder leading edge and connecting screws; the density is 1.2g / cm 3Carbon / carbon matrix 2, used for the subsequent preparation of the rudder frame; providing a density of 1.1 g / cm 3 Carbon / carbon matrix 3, used for the subsequent preparation of rudder skin;

[0097] (1) Carbon / carbon matrix 1, carbon / carbon matrix 2 and carbon / carbon matrix 3 are placed in a graphite crucible respectively, and are mixed with silicon alloy powder (particle size is 1 μm) at a mass ratio of 1:5, and reaction infiltration is carried out at 1500° C. to obtain ceramic matrix composite materials of a rudder leading edge, a connecting screw, a rudder frame and a rudder skin respectively; wherein the density of the ceramic matrix composite material of the rudder leading edge is 3.2 g / cm 3 The density of the ceramic matrix composite material of the connecting screw is 1.9g / cm 3 The density of the ceramic matrix composite material of the rudder frame and rudder skin is 1.95g / cm 3 ;

[0098] (2) respectively machining the prepared rudder leading edge, rudder skin, rudder frame and connecting screw ceramic matrix composite materials to obtain rudder leading edge, rudder skin, rudder frame and connecting screw structural parts; wherein the machining specification of the connecting screw is M6×1mm;

[0099] (3) The rudder leading edge, the rudder frame, and the rudder skin are assembled and connected using connecting screws to obtain a ceramic-based composite material air rudder.

[0100] Comparative Example 2

[0101] Comparative Example 2 is basically the same as Example 1, except that the connecting screws are tantalum-tungsten metal screws with a screw specification of M6×1 mm.

[0102] The components of the ceramic-based composite air rudder prepared in Examples 1 to 8 and Comparative Examples 1 to 2 were sampled and tested for performance. The test results are shown in Table 1.

[0103] Among them: the density test adopts the drainage method; the oxyacetylene antioxidant ablation resistance test is the mass ablation rate obtained by ablation at a high temperature of 2000℃ for 300s; the bending strength is tested in accordance with Q / SB 513-2013 "Test method for room temperature bending properties of continuous fiber reinforced ceramic matrix composites".

[0104] Table 1

[0105]

[0106] As shown in Table 1, the density of the ceramic matrix composite air rudder prepared by the present invention is 2.1 g / cm 3 The mass ablation rate of the ceramic matrix composite material of the rudder leading edge modified with hafnium in the 2000℃ oxyacetylene ablation test is less than 0.2×10-4 g / (cm 2 ·s), which makes the air rudder have excellent high temperature resistance and ablation resistance. The room temperature bending strength of the ceramic matrix composite material of the rudder frame and rudder skin is greater than 300MPa, which makes the air rudder have a high bearing capacity. At the same time, the connecting screws are formed by C / SiC ceramic matrix composite material, whose breaking load is greater than 4KN, and have good thermal matching performance with the rudder leading edge, rudder frame and rudder skin, thus ensuring the reliability of the air rudder connection.

[0107] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A ceramic matrix composite air rudder, characterized in that: The air rudder comprises a rudder leading edge, a rudder skin and a rudder frame, wherein the rudder skin and the rudder leading edge are connected to the rudder frame via connecting screws; wherein the rudder leading edge is formed by using a hafnium-modified C / SiC ceramic-based composite material, and the rudder skin, the rudder frame and the connecting screws are formed by using a C / SiC ceramic-based composite material.

2. The air rudder according to claim 1, characterized in that: The density of the ceramic matrix composite material of the rudder leading edge is 2.5-3.6g / cm 3 The density of ceramic matrix composite materials of rudder frame, rudder skin and connecting screws is 1.8-2.2g / cm 3 .

3. The air rudder according to claim 1, characterized in that: The hafnium-modified C / SiC ceramic-based composite material is prepared by the following method: using a hafnium-silicon precursor solution as an impregnation solution, and densifying a carbon / carbon matrix by an impregnation cracking method to obtain the hafnium-modified C / SiC ceramic-based composite material.

4. The air rudder according to claim 1, characterized in that: The C / SiC ceramic-based composite material is prepared by the following method: silicon alloy powder is used as reaction powder, and a reaction infiltration method is used to perform high-temperature infiltration on a carbon / carbon matrix to obtain the C / SiC ceramic-based composite material.

5. The air rudder according to claim 3 or 4, characterized in that: The carbon / carbon matrix is ​​prepared by depositing pyrolytic carbon on the surface of a carbon fiber preform by chemical vapor deposition; wherein the carbon fiber preform is woven in a needle-punched structure, a two-dimensional carbon cloth laminated stitching structure or a fine-woven puncture structure.

6. The air rudder according to claim 5, characterized in that: In the process of preparing the ceramic matrix composite material of the rudder leading edge and the connecting screw, the weaving method of the carbon fiber preform is a needle-punched structure, and the density of the carbon / carbon matrix is ​​0.6-0.85g / cm 3 ; In the process of preparing the ceramic matrix composite material of the rudder frame, the weaving method of the carbon fiber preform is a fine weaving puncture structure, and the density of the carbon / carbon matrix is ​​1.1-1.3g / cm 3 ; In the process of preparing the rudder skin ceramic matrix composite material, the weaving method of the carbon fiber preform is a two-dimensional carbon cloth laminated suture structure, and the density of the carbon / carbon matrix is ​​1.1-1.3g / cm 3 .

7. The air rudder according to claim 3, characterized in that: The hafnium silicon precursor solution comprises polyhafnium oxane, polycarbosilane, a carbon source precursor and an organic solvent; wherein the carbon source precursor is at least one of phenolic resin, furan resin and furfural resin, and the organic solvent is xylene; Preferably, the molar ratio of hafnium to silicon in the hafnium silicon precursor solution is (4-15):1, and the mass ratio of the sum of the amounts of polyhafnium oxane and polycarbosilane to the carbon source precursor and the organic solvent is (8-12):1:

1.

8. The air rudder according to claim 3, characterized in that: The viscosity of the hafnium silicon precursor solution is 40-180 mPa·s; The temperature of the impregnation and cracking is 1450-2000° C., and the number of impregnation and cracking rounds is 9-13 rounds.

9. The air rudder according to claim 4, characterized in that: The particle size of the silicon alloy powder is 0.1-6 μm, and the mass ratio of the carbon / carbon matrix to the silicon alloy powder is 1:(4-9); The temperature of the high-temperature infiltration is 1350-1700° C., and the time of the infiltration reaction treatment is 60-90 minutes.

10. A method for preparing a ceramic matrix composite air rudder according to any one of claims 1 to 9, characterized in that: The preparation method comprises: (1) Using a hafnium silicon precursor solution as an impregnation solution, the carbon / carbon matrix is ​​densified by an impregnation pyrolysis method to obtain a rudder leading edge ceramic matrix composite material; (2) Using silicon alloy powder as reactive powder, high-temperature infiltration was performed on carbon / carbon matrices of different densities by reactive infiltration method to obtain ceramic matrix composites of rudder skin, rudder frame and connecting screws respectively; (3) Mechanically processing the ceramic matrix composite materials of the rudder leading edge, the rudder skin, the rudder frame and the connecting screws respectively to obtain the rudder leading edge, the rudder skin, the rudder frame and the connecting screws structural parts; (4) Assembling and connecting the rudder leading edge, rudder frame, and rudder skin using the connecting screws to obtain the ceramic-based composite material air rudder.

Citation Information

Patent Citations

  • Preparation method of fiber enhanced ceramics base composite material sharp leading edge

    CN104003746A

  • Ablation-resistant modified C / SiC composite material and preparation method thereof

    CN112374901A

  • Preparation method of Hf-Ta-C reinforced C / SiC ceramic matrix composite material

    CN112457035A

  • Bionic aircraft rudder surface preparation method

    CN113071163A

  • C / HfC ultrahigh-temperature ceramic-based composite material and preparation method thereof

    CN113912407A